2015
DOI: 10.1208/s12249-015-0296-y
|View full text |Cite
|
Sign up to set email alerts
|

Formulation of Eco-friendly Medicated Chewing Gum to Prevent Motion Sickness

Abstract: ABSTRACT. An attempt was made to formulate medicated chewing gum to prevent motion sickness using natural gum base for faster onset of action and easy administration, anywhere and anytime, without access to water. To avoid the discard issue of gum cud, natural gum base of Triticum aestivum (wheat grain) was explored because of its biodegradable and biocompatible nature and easy availability. Prolamin, extracted from wheat, showed good chewing capacity, elasticity, high water retention capacity, antifungal acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…Previous in vitro work investigating the release of substances from medicated chewing gums has involved techniques varying from the two instruments, recognised by the European Pharmacopoeia, known as apparatus A and B [19], [24]- [25], [95], to the use of a pestle and mortar to pound the chewing gum in solution releasing the agent of interest [96]. When analysing these methods it was clear that the human physiological features with mechanics of mastication and six degrees of freedom that are possible with human mastication were not accounted for limiting their applicability to modeling MCG drug release from chewing.…”
Section: Discussionmentioning
confidence: 99%
“…Previous in vitro work investigating the release of substances from medicated chewing gums has involved techniques varying from the two instruments, recognised by the European Pharmacopoeia, known as apparatus A and B [19], [24]- [25], [95], to the use of a pestle and mortar to pound the chewing gum in solution releasing the agent of interest [96]. When analysing these methods it was clear that the human physiological features with mechanics of mastication and six degrees of freedom that are possible with human mastication were not accounted for limiting their applicability to modeling MCG drug release from chewing.…”
Section: Discussionmentioning
confidence: 99%
“…Chewing gum incorporated with various types of active ingredients is one such example of novel drug delivery. Medicated chewing gum (MCGs) is effective locally as well as systemically in dental caries, smoking cessation 28 , pain, obesity, acidity, allergy, nausea, motion sickness 21,22 , diabetes, anxiety, dyspepsia, osteoporosis, cough, common cold, etc. 16,17,18,19 .…”
Section: Quick Response Codementioning
confidence: 99%
“…The in-vitro drug release data revealed that MCG-II shows better drug release than other formulations. MCG -II formulation was considered to be an optimized formula that consists of synthetic gum base (60%), Liquid Glucose (20%), sucrose (15%) which shows more drug release in the phosphate buffer (pH 6.8) 21 . The cumulative drug release of MCG-II formulation was found to be 99.43%.…”
Section: Drugmentioning
confidence: 99%
“…Therefore, nowadays it can be stated that there are various food products that have improved their functional properties in the sectors, such as dairy, cereal, and meat products, different beverages, candies, cookies, pastries and baby foods . In this regard, the studies carried out with the aim of providing functionality to chewing gum have recently gained momentum . Since, chewing gum has many advantages in terms of targeted delivery of healthy ingredients without taking excess calories.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 In this regard, the studies carried out with the aim of providing functionality to chewing gum have recently gained momentum. 5,6 Since, chewing gum has many advantages in terms of targeted delivery of healthy ingredients without taking excess calories. For instance, it has a fast effect after absorption through the buccal and sublingual mucosal and from the gastrointestinal tract.…”
Section: Introductionmentioning
confidence: 99%